Pemanfaatan Botol Bekas Sebagai Media Tanaman Hidroponik Bersama Ibu-Ibu PKK Ampek Nagari - Rifdha Hayati; Martin Kustati; Nana Sepriyanti; Romi Hardianto (LPPI UMN AL WASHLIYAH, 2024)
The assistance provided to PKK mothers aims to introduce hydroponic plants to PKK mothers, increase the mothers' insight into hydroponic plants and build a sense of concern for plastic bottle waste. The methods used are the PAR (Participatory Action Research) method and the lecture method for delivering material directly. This assistance has resulted in increasing the enthusiasm of housewives to implement the knowledge gained and building a sense of concern for plastic waste. The material in this assistance is collaboration with hydroponic plant owners in the field to obtain detailed and accurate information.